Wave normal angles of whistler mode chorus rising and falling tones. Issue 12 (3rd December 2014) - Taubenschuss, Ulrich; Khotyaintsev, Yuri V.; Santolík, Ondrej; Vaivads, Andris; Cully, Christopher M.; Contel, Olivier Le; Angelopoulos, Vassilis
Abstract We present a study of wave normal angles (θk) of whistler mode chorus emission as observed by Time History of Events and Macroscale Interactions during Substorms (THEMIS) during the year 2008. The three inner THEMIS satellites THA, THD, and THE usually orbit Earth close to the dipole magnetic equator (±20°), covering a large range of L shells from the plasmasphere out to the magnetopause. Waveform measurements of electric and magnetic fields enable a detailed polarization analysis of chorus below 4 kHz. When displayed in a frequency‐θk histogram, four characteristic regions of occurrence are evident. They are separated by gaps at f/fc, e≈0.5 (f is the chorus frequency, fc, e is the local electron cyclotron frequency) and at θk∼40°. Below θk∼40°, the average value for θk is predominantly field aligned, but slightly increasing with frequency toward half of fc, e (θk up to 20°). Above half of fc, e, the average θk is again decreasing with frequency. Above θk∼40°, wave normal angles are usually close to the resonance cone angle. Furthermore, we present a detailed comparison of electric and magnetic fields of chorus rising and falling tones. Falling tones exhibit peaks in occurrence solely for θk>40° and are propagating close to the resonance cone angle. Nevertheless, when comparing rising tones to falling tones at θk>40°, the ratio of magnetic to electric field shows no significant differences. Thus, we conclude that falling tones are generated under similar conditions as rising tones, with common source regions close to the magnetic equatorial plane.